Entrepreneurial aspiration among asnaf students in UiTM Pahang / Faizan Abd Jabar, Suhanom Mohd Zaki, Musramaini Mustapha ... [et al.] - Abd Jabar, Faizan; Mohd Zaki, Suhanom; Mustapha, Musramaini; Abd Rahman, Muhammad Zahran; Syed Wahid, Sharifah Norhuda (Universiti Teknologi MARA Cawangan Pahang, 2016)
Aspiration or a strong desire for achievement is an attitude that should be commended. Aspirations to be an entrepreneur should be nurtured, supported and guided accordingly. Building and sustaining a business in not as easy as the theory made it out to be without the relevant knowledge and experience. However, in spite of the challenges, many individuals are still interested to venture in this field especially since the government has initiated various programs to assist them in starting a business. Entrepreneurship requires passion and a high level of patience which can be nurtured from young. As such, a research on the interest in starting a business among the Malays was conducted with a focus group covering Asnaf students from Universiti Teknologi MARA (Pahang). Asnaf students comprises of orphans and the poor that are eligible to receive zakat. This group was chosen based on their high aspiration to have a better life in the future. Based on a survey conducted through questionnaire, 96.61 percent have the aspirations to be involved in the business realm than venturing to other salaried paid jobs. This entrepreneurial aspiration may be driven by UiTM (Pahang)’s various activities to foster their interest in the field of business. Therefore, the interest among the Asnaf students requires the support from various parties in order for them to realise the dream of owning their own business in the future.